Second-Best Income Taxation with Endogenous Human Capital and Borrowing Constraints - Bas Jacobs; Hongyan Yang (Center for Economic Studies and ifo Institute (CESifo), 2013)
We formulate a two-period life-cycle model of saving, labor supply, and human capital investments when individuals differ in ability and initial wealth. Borrowing constraints prevent individuals to optimally smooth consumption over the life-cycle and to optimally invest in human capital. We show that the optimal linear income tax is positive - even in the absence of any redistributional concerns. A progressive income tax is efficient because it relaxes borrowing constraints by redistributing resources from the unconstrained to the borrowing constrained stages of the life-cycle. Hence, consumption is smoothed better and investments in human capital increase. The progressive income tax is a second-best instrument to correct the non-tax distortion in the capital market. The equity-efficiency trade-off is therefore less severe when progressive income taxes mitigate capital market imperfections. Simulations demonstrate that optimal income taxes are substantially higher when they alleviate credit constraints.
Keywords: H21; I20; J20; 330; labor taxation; human capital investment; credit constraints